2014
DOI: 10.1017/s0033291714000592
|View full text |Cite
|
Sign up to set email alerts
|

Understanding jumping to conclusions in patients with persecutory delusions: working memory and intolerance of uncertainty

Abstract: Background. Persecutory delusions are a key psychotic experience. A reasoning style known as 'jumping to conclusions' (JTC) -limited information gathering before reaching certainty in decision making -has been identified as a contributory factor in the occurrence of delusions. The cognitive processes that underpin JTC need to be determined in order to develop effective interventions for delusions. In the current study two alternative perspectives were tested: that JTC partially results from impairment in infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 47 publications
3
39
0
3
Order By: Relevance
“…Regarding the data-gathering bias, only the Rocha trial (Rocha & Queiros, 2013) found a significant effect, but also showed a worsening of positive symptoms instead of a reduction. Freeman et al (2014) reported that only 24% of delusional patients showed a data-gathering bias and that this was associated with deficits in working memory, lower intelligence quotient, lower levels of tolerance for uncertainty, and lower worry. Freeman et al (2014) reported that only 24% of delusional patients showed a data-gathering bias and that this was associated with deficits in working memory, lower intelligence quotient, lower levels of tolerance for uncertainty, and lower worry.…”
Section: Main Findingsmentioning
confidence: 99%
“…Regarding the data-gathering bias, only the Rocha trial (Rocha & Queiros, 2013) found a significant effect, but also showed a worsening of positive symptoms instead of a reduction. Freeman et al (2014) reported that only 24% of delusional patients showed a data-gathering bias and that this was associated with deficits in working memory, lower intelligence quotient, lower levels of tolerance for uncertainty, and lower worry. Freeman et al (2014) reported that only 24% of delusional patients showed a data-gathering bias and that this was associated with deficits in working memory, lower intelligence quotient, lower levels of tolerance for uncertainty, and lower worry.…”
Section: Main Findingsmentioning
confidence: 99%
“…In this respect, it has been suggested that data-gathering bias represents a key cognitive component in delusion formation and maintenance 6 . Although most of the studies endorsing this association used a cross-sectional design, comparing those with and without delusions in samples of patients with schizophrenia or other psychoses 7,8 , meta-analyses mostly found a weak association with delusions, yet a clear association with psychosis 1,3,9,10 . Moreover, jumping to conclusions was found not only in non-delusional and remitted patients with schizophrenia, but also in individuals at clinical high risk and first-degree relatives [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Many subsequent studies have confirmed this finding (for a review see Garety & Freeman, 2013). However, in much the same way as with theory of mind impairment, these studies have struggled to demonstrate an association with presence or severity of delusions (Dudley et al, 2011; Falcone et al, 2015; Freeman et al, 2014; Garety et al, 2013; Langdon, Ward, & Coltheart, 2010; Lincoln, Ziegler, Mehl, & Rief, 2010; Menon, Pomarol-Clotet, McKenna, & McCarthy, 2006; Moritz & Woodward, 2005; Mortimer et al, 1996; Ochoa et al, 2014; Peters, Thornton, Siksou, Linney, & MacCabe, 2008; So et al, 2012). …”
Section: Theories Of Delusionsmentioning
confidence: 99%